Augmented Reality in Primary Science Education: A Systematic Development Study Using Assemblr Edu Platform - Zantika Zulmi; Nurul Fitriah Aras; Sinta Satria Dewi Pendit; Abdul Rahman; Ryan Andika Pratama (Journal of Innovation and Research in Primary Education, 2026)
Conventional science instruction in Indonesian elementary schools often fails to adequately engage students, particularly when teaching complex anatomical concepts requiring three-dimensional visualization. This study developed and evaluated Assemblr Edu-based Augmented Reality (AR) learning media for the five senses topic in fourth-grade science education. Employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the research was conducted at Karuna Dipa Elementary School, Palu, involving 16 fourth-grade students. Expert validation assessed media validity through structured questionnaires. Practicality was evaluated via user response questionnaires from six students and one teacher. Effectiveness was measured through pre-test/post-test design with Normalized Gain (N-Gain) analysis. Expert validation yielded exceptional validity scores: material expert (99.3%) and media expert (91.6%), with a combined average of 95.45%. User practicality assessments showed high scores from students (90.41%) and teacher (92.5%). Learning outcomes demonstrated substantial improvement, with average pre-test scores of 65.3% increasing to 94% post-test, resulting in an N-Gain of 0.827, categorized as high effectiveness. The Assemblr Edu-based AR media proved highly valid, practical, and effective for enhancing elementary students' science learning outcomes. The systematic ADDIE-guided development process produced instructional media that significantly improved student engagement and conceptual understanding, providing a replicable model for integrating immersive technologies in resource-constrained educational contexts.